The effectiveness of communicative language approach in enhancing English speaking skills of EFL adult learners in Egypt - Marwa Mohamed Hassan Hedia (Insights into Language, Culture and Communication, 2022)
This research aims at investigating the effectiveness of using communicative activities in developing the English speaking ability of Egyptian college students. The study adopted the quasi-experimental pretest- posttest control group design. A group of 40 first year college students were selected from a private university in Cairo in the Academic year 2016- 2017 (20 students in the experimental group and 20 students in the control group). Students of the experimental group were taught by means of the proposed program of the current study; while students in the control group received regular instruction. The equipment and materials consisted of a pre-posttest administered to both groups before and after the treatment and an analytic speaking rubric for assessment. Quantitative data collected were statistically analyzed to validate the research hypotheses. Results of data analysis revealed that the experimental group students outperformed their control group counterparts in overall speaking proficiency. There were statistically significant differences between the mean scores of the experimental group on the pre-posttest in favor of the post- test scores.